2021
DOI: 10.1088/1757-899x/1114/1/012088
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous two-phase extraction of lead from contaminated aqueous solutions

Abstract: Aqueous two-phase extraction is an ecologically safe method for heavy metal recovery and regeneration from contaminated aqueous solutions. Investigation has been carried out experimentally for the extraction of lead from aqueous solutions using Polyethylene Glycol 1500-Ammonium sulfate two-phase system. The extracting agent used is sodium chloride. Aqueous two-phase extraction experiments for Pb(II) have been performed in batch mode according to the central composite design under Response Surface Methodology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…The highest extraction efficiency of 74.7% was observed for the ATPS containing (NH 4 ) 2 SO 4 . Compared with the previous studies summarized in Table 1, this result is significantly higher than that for other ATPS based on polyethylene glycol 24,25 but lower than some ATPS based on octyl phenol ethoxylate. 23 The second-highest extraction was achieved for the MgSO 4 system.…”
Section: Partition Coefficient (K Pb ) and Extraction Efficiency (%Ee...contrasting
confidence: 75%
See 2 more Smart Citations
“…The highest extraction efficiency of 74.7% was observed for the ATPS containing (NH 4 ) 2 SO 4 . Compared with the previous studies summarized in Table 1, this result is significantly higher than that for other ATPS based on polyethylene glycol 24,25 but lower than some ATPS based on octyl phenol ethoxylate. 23 The second-highest extraction was achieved for the MgSO 4 system.…”
Section: Partition Coefficient (K Pb ) and Extraction Efficiency (%Ee...contrasting
confidence: 75%
“…To the best of our knowledge, there is only one report on using aqueous biphasic systems based on polyethylene glycol, namely, PEG1500/(NH 4 ) 2 SO 4 and PEG1500/ NaCl, to extract lead ions. 25 The authors reported that the maximum extraction yield was 51.8%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial concentration of the salt phase was 9.8 g/L. [46] Shahrokhi et al investigated copper extraction in aqueous two-phase systems using polyethylene glycol-zinc sulphate in the presence of ammonium thiocyanate extractant. According to the reports provided by the design of the central composite experiment, the highest extraction efficiency of copper ions was obtained under the specified conditions of pH = 4.7, the molecular weight of polyethylene glycol 6000, the concentration of polyethylene 20, and the salt concentration of 15, 93.3%.…”
Section: Introductionmentioning
confidence: 99%